Assessing the risk of Fusarium oxysporum f. sp. cubense Tropical Race 4 outbreaks in Ecuadorian banana crops using spatial climatic data - Fernández-Ledesma, Cindy M. (2023)
The Musaceae family is susceptible to Fusarium wilt (Fw), which is considered the most important disease globally, caused by a group of Fusarium species that includes F. oxysporum f. sp. cubense tropical race 4 (FocTR4). Until recently, FocTR4 was not present in Latin America. However, wilting, chlorosis of leaves, and vascular discoloration (typical symptoms of Fw) were observed in at least a hundred Cavendish plants located in Colombia, Peru and Venezuela in 2019, 2021 and 2022, respectively. Normally, the disease is more severe throughout the warmer and rainy months of the year. Since Ecuador is the world's leading exporter of bananas, including plantains, this study aimed to identify agroclimatic favorability zones for FocTR4 potential incidence in the country, testing linear models to evaluate disease occurrence in relation to climatic conditions and map favorability zones. Most of the banana-producing provinces, including Guayas, Los Ríos, El Oro, Manabí, Santa Elena, and Esmeraldas, presented an estimate ranging from medium-low to very high. In Guayas and Los Rios, the agroclimatic favorability zones of the main Ecuadorian producer provinces for a very high-risk account for almost 50%. This information can help make preventive management decisions in zones with a greater risk of spreading FocTR4.